142k views
5 votes
For the function f(2)-2+2, x > 03x + 2, 3 < 0what is the average rate of change over the interval 1 sxs 3?average rate of change = 1

For the function f(2)-2+2, x > 03x + 2, 3 < 0what is the average rate of change-example-1
User Rizza
by
4.7k points

1 Answer

2 votes

average rate of change = -1

Step-by-step explanation:

Average rate of change formula:


\frac{f(b)\text{ - f(a)}}{b-a}=(f(3)-f(1))/(3-1)

The range is from 1 to 3.

b= 3, a = 1

From the given function, x is greater than 1 when f(x) = -x + 2

when x = 3

f(3) = -3 + 2 = -1

when x = 1

f(1) = -1 + 2 = 1


\begin{gathered} \text{Average rate of change = }\frac{-1\text{ -1}}{3-1}=(-2)/(2) \\ \text{Average rate of change =}-1 \end{gathered}

User Jan Gerlinger
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.